Pet ownership issues encountered by geriatric professionals: Preliminary findings from an interdisciplinary sample - Bibbo, Jessica; Johnson, Justin; Drost, Jennifer C.; Sanders, Margaret; Nicolay, Sarah (Frontiers in Psychology, 2022)
Pets often factor in older adults’ health behaviors and decisions. However, the degree to which issues related to pet ownership are encountered or addressed by professionals working with this population remains unknown. The aim of this study was to identify specific issues stemming from pet ownership professionals have encountered in their work with older adults, people living with dementia, and care partners. An interdisciplinary (e.g., social services, healthcare) sample (N = 462, 89.13% female, Mage = 53.02, SDage = 12.18) completed an online survey addressing pet ownership issues encountered in their work. Descriptive statistics, t-tests, and repeated measures ANOVAs were used to analyze quantitative data. A conventional content analysis was used to analyze open-ended responses to an item asking about “other” issues encountered in their work with these populations. The professionals estimated 46.29% of clients had been pet owners, 41.23% regularly asked about pets, and 79.22% had encountered issues related to pet ownership. Specific issues raised to the professionals varied by type of client. The professionals reported older adults most often raised getting pet items into the home and concerns about their pets’ health. The issues most often raised by people living with dementia to the professionals were planning for the pet due to a housing transition and basic pet care. Care partners focused on basic pet care and planning for the pet due to a housing transition. The professionals themselves most often raised the issues of basic pet care, concerns about falling, and the pets’ behavior. Professionals who entered clients’ homes were more likely to raise issues stemming from pet ownership compared to those who did not enter clients’ homes (t(429.40) = 5.59, p < .00001). The eleven newly identified issues (e.g., pets impeding care, people refusing care due to the pet) underscored how the health and wellbeing of people and their pets are linked. The results of this study provide strong evidence that do encounter issues related to pet ownership. Including issues stemming from pet ownership into procedures, policies, and programs is likely to have positive impacts on those served by and working in the geriatric workforce.